A novel putter design to minimise range variability in golf putts - Emerson, N. J.; Morris, T.; Potts, J. R. (Proceedings, 2018)
Putting accounts for more shots in a round of golf than any other type of play. The percentage of putts holed decreases as putt length increases, because golfers struggle to achieve a consistent range and direction. Range variation has been partly attributed to the ball striking the club face away from the central plane of the putter face. Tests have shown a 30 mm off-centre impact can reduce the roll distance of a putt by 13%. In this paper, changes in mass distribution of the putter body and the addition of a flexible striking surface are considered. Physical testing and Finite Element Analysis are used to produce a club design with more consistent roll distance. Redistribution of mass reduced the roll distance variation across the clubface. Combining this with a flexible impact surface reduced the variation between a central impact and one 20 mm from center to just 1%. The proposed design could significantly reduce distance variation; aiding golfers in holing putts. Future work will optimise the design and validate through physical prototyping.